2016
DOI: 10.5424/sjar/2016141-8859
|View full text |Cite
|
Sign up to set email alerts
|

Indole-3-acetic acid (IAA) producing Pseudomonas isolates inhibit seed germination and α-amylase activity in durum wheat (Triticum turgidum L.)

Abstract: <p>The role of plant-associated bacteria in plant physiology and metabolism is well documented, but little has been known about the roles played by <em>Pseudomonas</em> in durum wheat (<em>Triticum turgidum</em> L. var <em>durum</em>) growth and development. An<em> in vitro</em>experiment was conducted to observe the effect of the inoculation of four indole-3-acetic acid (IAA)-producing <em>Pseudomonas </em>isolates<em> </em>and exog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 35 publications
0
26
1
3
Order By: Relevance
“…The results showed that the supernatant of eight isolates from H. perforatum inhibited seed germination and seedling growth of tomato. Similarly, Tabatabaei et al (2016) observed an inhibition of seed germination and seedling growth of durum wheat by Pseudomonas sp. UW3, P. fluorescent 550, and Pseudomonas sp.…”
Section: Discussionmentioning
confidence: 86%
“…The results showed that the supernatant of eight isolates from H. perforatum inhibited seed germination and seedling growth of tomato. Similarly, Tabatabaei et al (2016) observed an inhibition of seed germination and seedling growth of durum wheat by Pseudomonas sp. UW3, P. fluorescent 550, and Pseudomonas sp.…”
Section: Discussionmentioning
confidence: 86%
“…The IAA seems to play a double role according to its concentration (Chauan et al, 2009). High concentrations of IAA secreted by bacteria inhibit the germination of weed seeds (Tabatabaei et al, 2016), and are also produced by most plant growth-promoting bacteria (PGPB), being considered one of the most effective mechanisms already elucidated (Lin et al, 2012). At high concentrations, the IAA can also reduce plant root growth by its relationship with ethylene synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…An increase was quantified in all the growth parameters of the ancho-type pepper plants inoculated with marine bacteria and yeasts. This marine microorganism's capacity to increase plant growth is related to different mechanisms, among which hormone production is important (of hormones such as indole ascetic acid (IAA) and gibberellins [51]), as well as phosphate solubilization [52] and atmospheric nitrogen fixation to soil [53], among others. With respect to the bacteria, several studies have reported the capacity of S. rhizophila to promote plant growth in cucumber [54], soy [55], and basil [29], as well as the different Bacillus species effects on the growth of tomato [56], wheat [57], and banana [58].…”
Section: Discussionmentioning
confidence: 99%